Viral Shedding in Mice following Intravenous Adenovirus Injection: Impact on Biosafety Classification - Christopher J. LaRocca; Kari L. Jacobsen; Kazuho Inoko; Stanislav O. Zakharkin; Masato Yamamoto; Julia Davydova (Viruses, 2023)
There have been numerous advances in gene therapy and oncolytic virotherapy in recent years, especially with respect to cutting-edge animal models to test these novel therapeutics. With all of these advances, it is important to understand the biosafety risks of testing these vectors in animals. We performed adenovirus-based viral shedding studies in murine models to ascertain when it is appropriate to downgrade the animals from Biosafety Level (BSL) 2 to BSL 1 for experimental handling and transport. We utilized intravenous injections of a replication-competent adenovirus and analyzed viral shedding via the collection of buccal and dermal swabs from each animal, in addition to obtaining urine and stool samples. The adenovirus hexon copy number was determined by qPCR, and plaque formation was analyzed to assess the biologic activity of viral particles. Our results demonstrate that after 72 h following viral inoculation, there is no significant quantity of biologically active virus shedding from the animals. This observation suggests that on day 4 following adenovirus injection, mice can be safely downgraded to BSL 1 for the remainder of the experiment with no concern for hazardous exposure to laboratory personnel.